2006
DOI: 10.1111/j.1471-8847.2006.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and Regulatory Issues Surrounding African Traditional Medicine in the Context of Hiv/Aids

Abstract: It has been estimated that more than 80% of people in Africa use traditional medicine (TM). With the HIV/AIDS epidemic claiming many lives in Africa, the majority of people affected rely on TM mainly because it is relatively affordable and available to the poor populations who cannot afford orthodox medicine. Whereas orthodox medicine is practiced under stringent regulations and ethical guidelines emanating from The Nuremburg Code, African TM seems to be exempt from such scrutiny. Although recently there have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 34 publications
(16 reference statements)
0
29
0
Order By: Relevance
“…Collaboration between these two practices has been initiated in many SSA countries but reservations about the results have been raised (Nyika, 2007). The health systems in SSA lack human resources to face the increasing needs to care for people living with HIV (Vassall & Compernolle, 2006) and the World Health Organization (WHO) has since 1974 acknowledged the importance of traditional health practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration between these two practices has been initiated in many SSA countries but reservations about the results have been raised (Nyika, 2007). The health systems in SSA lack human resources to face the increasing needs to care for people living with HIV (Vassall & Compernolle, 2006) and the World Health Organization (WHO) has since 1974 acknowledged the importance of traditional health practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the people of African descent patronize herbal or traditional medicine for their health needs. It is estimated that 70-80% of patients in Africa are treated by traditional healers and herbal practitioners (Diallo et al, 1996;Nyika, 2007). Furthermore, about 40% of all medicines on the market today have been derived directly or indirectly from natural sources; 25% being from plants, 13% from microorganisms and 2% from animals (De Smet, 1997;Pandey, 1998;Shu, 1998;Blumenthal, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Mthatha 5117, South Africa; Tel: (+27) 475022794 / (27) 726373725; Fax: (+27)502 2758; E-mail: bnkehchungaga@wsu.ac.za hospitals is not readily available, this makes the traditional healers the care givers of choice [7]. Indeed, it is reported that more than 80% of Africans, including Cameroonian, make use of one kind of alternative therapy or the other from traditional healers [8]. Current WHO reports show that there is an increasing trend across the world for the use of traditional and alternative medicines [9].…”
Section: Introductionmentioning
confidence: 99%